Productive Role Of Coastal Women In Development Communication (Case Study of Empowerment of Fisher Housewives in Building the Family Economy in Pabeanudik Village, Indramayu District) - Liliyana Liliyana; Veranus Sidharta; Wenny Maya Arlena; Ferrari Lancia; Abdul Aziz (Sean Institute, 2023)
Pabeanudik Village is located in the Indramayu sub-district, a coastal area where most of the people are fishermen and to fulfil their household needs depend on fishing activities. With the potential of marine resources that are adequately owned, the welfare of the household and the economy of the people who live on the coast can be fulfilled. However, this only applies to a few people living in coastal areas who are still below the poverty line. This is because fishermen depend on the sea where weather conditions are uncertain and marine catches are not optimal or even non-existent, hindering the development of family economic welfare. In an uncertain economic situation, fishing families are required to be able to adapt to be able to build a family economy so that daily survival can be fulfilled. This study aims to describe the empowerment of women in their role in building the economy of fishermen's families through fish management businesses in Pabeanudik Village, Indramayu District. This study uses a qualitative descriptive method through an instrumental case study approach. This study concludes that the empowerment of coastal women in Pabeanudik village is reflected in their productive role in the fish management business, which is carried out to obtain additional economic income to meet the needs of family life.